The Status of Representative Anode Materials for Lithium‐Ion Batteries - Du, Chenyu; Zhao, Zengying; Liu, Hao; Song, Fangyu; Chen, Leilei; Cheng, Yan; Guo, Zhanhu (Chemical record, 2023)
Since the invention of lithium‐ion batteries as a rechargeable energy storage system, it has uncommonly promoted the development of society. It has a wide variety of applications in electronic equipment, electric automobiles, hybrid vehicles, and aerospace. As an indispensable component of lithium‐ion batteries, anode materials play an essential role in the electrochemical characteristics of lithium‐ion batteries. In this review, we described the development from lithium‐metal batteries to lithium‐ion batteries in detail on the time axis as the first step; This was followed by an introduction to several commonly used anode materials, including graphite, silicon, and transition metal oxide with discussions the charge‐discharge mechanism, challenges and corresponding strategies, and a collation of recent interesting work; Finally, three anode materials are summarized and prospected. Hopefully, this review can serve both the newcomers and the predecessors in the field. The current status of the development of graphite, silicon, and transition metal oxide anodes based on lithium‐ion batteries is discussed.